Perbedaan Daya Hambat Obat Anestesi Lokal Lidocaine 2% dan Articaine 4% Terhadap Pertumbuhan Bakteri Porphyromonas Gingivalis Secara In Vitro - Fairuza Muharammy; Rizanda Machmud; Surya Nelis (Faculty of Dentistry Universitas Andalas, 2016)
Porphyromonas gingivalis is a gram-negative anaerobic bacteria which is an oral normal microflora located in subgingival area.This bacteria can cause inflamation and delayed wound healing after dental invasive procedures. Lidocaine 2% and articaine 4% are the most used anaesthetic agents in dentistry. Both of these agents have been studied for having antibacterial effect in certain concentrations. This will open the possibility of using local anaesthetic agents as antibacterial agent in dental invasive procedures to prevent infection after procedures. The purpose of this study is to analyze the difference inhibition of local anaesthetics drug lidocaine 2% and articaine 4% on the growth of Porphyromonas gingivalis bacteria in vitro. The study subject was pure culture of Porphyromonas gingivalis ATCC 33277 divided by two group, one group with lidocaine 2% and other with articaine 4%. This study was experimental laboratory with post test only control group design. The mean of inhibitions were obtained by measuring inhibition zone formed around paper discs with caliper in milimeter scale. The result showed Inhibition rate lidocaine 2% had greater rate than articaine 4% in inhibiting the growth of Porphyromonas gingivalis bacteria in vitro.The conclusion was lidocaine 2% was more effective than articaine 4% in inhibiting the growth of Porphyromonas gingivalis bacteria in vitro.